Design and formulation of polymeric nanosponge tablets with enhanced solubility for combination therapy. Issue 57 (21st September 2020) - Moin, Afrasim; Roohi, N. K. Famna; Rizvi, Syed Mohd Danish; Ashraf, Syed Amir; Siddiqui, Arif Jamal; Patel, Mitesh; Ahmed, S. M.; Gowda, D. V.; Adnan, Mohd
Abstract : Polymeric nanosponges as potential carriers for successful combination therapy of poorly soluble drugs (paracetamol, aceclofenac, caffeine). Abstract : Three drugs namely caffeine, paracetamol, and aceclofenac are commonly used for treating various acute and chronic pain related ailments. These 3 drugs have varied solubility profiles, and formulating them into a single tablet did not have the desired dissolution profile for drug absorption. The objective of the present research was to tailor the drug release profile by altering drug solubility. This was achieved by loading the drug into nanosponges. Here, three-dimensional colloidal nanosponges were prepared using β-cyclodextrin with dimethyl carbonate as a cross-linker using the hot-melt compression method. The prepared nanosponges were characterized by FTIR, 1 H NMR spectroscopy, DSC, XRPD studies and SEM. The FTIR and DSC results obtained indicated polymer-drug compatibility. The 1 H NMR spectroscopy results obtained indicated the drug entrapment within nanosponges with the formation of the inclusion complex. XRPD studies showed that the loaded drug had changed crystalline properties altering drug solubility. SEM photographs revealed the porous and spongy texture on the surface of the nanosponge. Box–Behnken experimental design was adopted for the optimization of nanosponge synthesis. Among the synthesized nanosponges containing paracetamol, aceclofenac and caffeine, batch F3–P31, F3–A31 and F3–C31 were considered optimized. Their particle size was 185, 181 and 199 nm with an entrapment efficiency of 81.53, 84.96, and 89.28% respectively. These optimized nanosponges were directly compressed into tablets and were studied for both pre and post-compression properties including in vitro drug release. The prepared tablet showed desired drug dissolution properties compared to the pure drug. The above outcomes indicated the applicability of nanosponges in modulating the drug release with varied solubility for combination therapy.